A revised checklist of Lepanthes (Orchidaceae) from Peru, including new country records - Ocupa-Horna, L.; Thoerle, L.; Schuiteman, A.; Martel, C. (Springer, 2023)
We present a checklist of species of Lepanthes (Orchidaceae) from Peru, based on published reports supplemented by personal observations and the review of some herbarium specimens. Of the 81 species here reported from Peru, five are new records for the country and 44 are endemic. For each recorded species, we provide the accepted name, publication data, type, synonymy, and distribution in Peru by department and extralimital distributions by country. A map showing the numerical distribution of species by department and photographs of the five newly recorded and one recently described species are also provided. One lectotype is designated.
Keywords: Andes; endemic species; montane forest; Pleurothallidinae; subgenus Lepanthes; subgenus Marsipanthes; https://purl.org/pe-repo/ocde/ford#1.06.13